IMPROVING KNOWLEDGE OF ADOLESCENT WOMEN ABOUT MENSTRUATION THROUGH HEALTH PROMOTION - Marlita Dewi Lestari; Alya Ainurokhmah; Berta Lisna Suruklusy; Diah Rahayu Ningsih; Khoirul Anwar; Putri Novia; Riza Ismi Dwi Novalia; Sri Wahyuni (Community Service Journal of Indonesia, 2019)
Menstrual Health Promotion Activities for Adolescent Women at the 2nd Junior High School of Buduran, Sidoarjo is a form of community service in the form of counseling aimed at growing and enhancing healthy behavior in adolescents, especially in recognizing the phase of menstruation in adolescent women. The implementation of these activities on December 4, 2018 took place at the 2nd Junior High School of Buduran, Sidoarjo. The target is 7th grade students of the 2nd Junior High School of Buduran, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for 3 weeks before the activity is carried out, starting from the selection of health counseling materials to the submission of licensing to the relevant parties. As an evaluation, the activity was attended by 44 students and 1 teacher, participants participated in the activity with enthusiasm and conducive, the activity can be carried out on time smoothly. Keywords: Women’s youth knowledge, health promotion, menstruation.